2010
DOI: 10.1524/ract.2010.1683
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ionic strength on complexation of Pu(IV) with humic acid

Abstract: International audienceSuccessful geochemical modelling of the migration of radioactive materials, such as the transuranic elements, from nuclear waste repositories is dependent upon an understanding of their interaction with biogeopolymers such as humic acids, the most likely complexing agents in groundwaters. An established silica/humic acid composite has been evaluated as a model substrate for naturally occurring humate-coated minerals that are likely to be present in the vicinity of the repositories. The bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 26 publications
2
22
0
Order By: Relevance
“…Reiller et al (2008) reviewed all the available tetravalent actinide (An(IV)) complexation data with HA and found a high consistency between them. More recent Pu(IV)-HA binding studies are in relatively good agreement with the latter observation (Szabó et al, 2010;Sasaki et al, 2012). In these references, Pu(IV)-HA interaction is described in terms of complexation of mononuclear Pu with humic acid.…”
Section: Introductionsupporting
confidence: 65%
“…Reiller et al (2008) reviewed all the available tetravalent actinide (An(IV)) complexation data with HA and found a high consistency between them. More recent Pu(IV)-HA binding studies are in relatively good agreement with the latter observation (Szabó et al, 2010;Sasaki et al, 2012). In these references, Pu(IV)-HA interaction is described in terms of complexation of mononuclear Pu with humic acid.…”
Section: Introductionsupporting
confidence: 65%
“…In a recent solubility study, Kobayashi et al suggested the presence of ternary Th(OH) 2 (L) 0 as the solubility-limiting solid phase, where L represented the dicarboxylic acids, while the aqueous species was assumed to be the binary complex Th(L) p , instead of Th(OH) n (L) p , for better convergence of the solubility fitting analysis [1,12]. In the humic acid system, Szabó et al discussed the formation constant of Pu(IV) and the contribution of hydrolysis [13]. On the basis of a strong hydrolysis effect, they believed that Pu(OH) + 3 was the predominant species, and then surmised that the ternary complex was Pu IV (OH) 3 (L).…”
Section: Theoreticalmentioning
confidence: 99%
“…The E h value of the aqueous phase in the Pu system was measured using a couple consisting of Pt and Ag/AgCl electrodes after calibration with a redox standard solution containing the redox couple ferricyanide/ferrocyanide [11]. [11], and the state in the presence of humic acid has been suggested in the literature [13]. Since the mass balance of Th at pH c > 3 was more than 90% in back-extraction, no major unexpected reactions such as adsorption of colloids on the polypropylene vessel wall or precipitation at the liquidliquid interface were observed.…”
Section: Solvent Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their solubility study, Kobayashi et al suggested the formation of binary Th-L and/or ternary Th-OH-L complexes as the solubility-limiting solid phase, where the dicarboxylic acids (L 2− ) were oxalic, glutaric, and adipic acids for the binary system and succinic and glutaric acids for the ternary system [25,26]. For Pu 4+ , a ternary 1 : 1 : 1 complex of Pu 4+ -OH-L was assumed to form in a complexation study of Pu 4+ with L 2− at lower pH values [27], and Szabó et al selected Pu 4+ -(OH) 3 -HA in their study of an HA system [28]. Also, Marsac et al discussed the complexation of Pu 4+ and proposed a ternary complex such as Pu 4+ -(OH) 2 -ALHA and its polynuclear species under weakly acidic conditions [29].…”
Section: Selection Of ( ) Values For Each Metal Ionmentioning
confidence: 99%